Analisis Pengaruh Minat dan Motivasi Terhadap Keputusan Memilih Program Studi Dimediasi Variabel Pekerjaan Yang Diharapkan - Merta Kusuma; Tezar Arianto; Meilaty Finthariasari (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2021)
Background – Every prospective student is free to make their choice to choose the faculty and study program they are interested in, which of course is in accordance with their abilities academically and financially. This research was conducted based on the research gap found by the researcher. Baker (2018) suggests further research to analyze the expected job variables as a factor in choosing decisions. Objective - To analyze the direct and indirect effect between each variable Interest, motivation, and expected job on the decision to choose. Design/ Methodology/ Approach – This research is a descriptive quantitative research. The population in this study were new students in the 2020 academic year at the Faculty of Economics at five universities in Bengkulu City. Samples were drawn using the Slovin formula as many as 356 respondents. Results and Discussion – The results of this study indicate that the higher the interest of individuals (students) it will encourage them to decide what they want, so it is said that interest is one of the factors that encourage someone to choose something. Likewise, student motivation in studying can be a determinant of their success in the future. The expected job is an important driving factor for students in choosing the faculty they will take in gaining knowledge. This is evidenced by the results of the current study and strengthened by the results of previous studies. Conclusion – There is a significant effect between each of the expected interest, motivation, and work variables on the decision to choose, with values ​​of 0.596, 0.452, 0.580, respectively. Then the work variable which is expected to be able to mediate between the interest and motivation variables on the decision to choose, with values ​​of 0.507 and 0.566, respectively. Research implications - The expected work variables in this study can provide information to each university that is the object of research that is not only related to student internal factors but there are other external factors that have an important contribution to the decision to choose prospective students in determining their choice to take college. Thus, universities and faculties can establish cooperation with job providers to accommodate quality graduates in the future, so that this can increase interest and motivation in determining college choices at universities in Bengkulu City. Research limitations - This research is limited to the Bengkulu City area with a total sample of 356 respondents and the number of variables studied is only two independent variables (interest and motivation), one mediating variable (expected job), and one dependent variable (decision). choose).